Solo self-employment and alternative work arrangements: A cross-country perspective on the changing composition of jobs - Boeri, Tito, et al (The Journal of Economic Perspectives)
The nature of self-employment is changing in most OECD countries. Solo self-employment is increasing relative to self-employment with dependent employees, often being associated with the development of gig economy work and alternative work arrangements. We still know little about this changing composition of jobs. Drawing on ad-hoc surveys run in the UK, US, and Italy, we document that solo self-employment is substantively different from self-employment with employees, being an intermediate status between employment and unemployment, and for some, becoming a new frontier of underemployment. Its spread originates a strong demand for social insurance which rarely meets an adequate supply given the informational asymmetries of these jobs. Enforcing minimum wage legislation on these jobs and reconsidering the preferential tax treatment offered to self-employment could discourage abuse of these positions to hide de facto dependent employment jobs. Improved measures of labor slack should be developed to acknowledge that, over and above unemployment, some of the solo self-employment and alternative work arrangements present in today's labor market are placing downward pressure on wages.
Keywords: Labor Demand, Wage Level and Structure, Wage Differentials